Immunomodulating and Revascularizing Activity of Kalanchoe pinnata Synergize with Fungicide Activity of Biogenic Peptide Cecropin P1 - N. S. Zakharchenko; A. S. Belous; Y. K. Biryukova; O. A. Medvedeva; A. V. Belyakova; G. A. Masgutova; E. V. Trubnikova; Y. I. Buryanov; A. A. Lebedeva (Journal of Immunology Research)
Previously transgenic Kalanchoe pinnata plants producing an antimicrobial peptide cecropin P1 (CecP1) have been reported. Now we report biological testing K. pinnata extracts containing CecP1 as a candidate drug for treatment of wounds infected with Candida albicans. The drug constitutes the whole juice from K. pinnata leaves (not ethanol extract) sterilized with nanofiltration. A microbicide activity of CecP1 against an animal fungal pathogen in vivo was demonstrated for the first time. However, a favorable therapeutic effect of the transgenic K. pinnata extract was attributed to a synergism between the fungicide activity of CecP1 and wound healing (antiscar), revascularizing, and immunomodulating effect of natural biologically active components of K. pinnata. A commercial fungicide preparation clotrimazole eliminated C. albicans cells within infected wounds in rats with efficiency comparable to CecP1-enriched K. pinnata extract. But in contrast to K. pinnata extract, clotrimazole did not exhibit neither wound healing activity nor remodeling of the scar matrix. Taken together, our results allow assumption that CecP1-enriched K. pinnata extracts should be considered as a candidate drug for treatment of dermatomycoses, wounds infected with fungi, and bedsores.